Interim Report from Burden of Obstructive Lung Disease (BOLD Study) in Tehran: Prevalence and Risk Factors of Chronic Obstructive Pulmonary Disease - Sharifi, Hooman (Tanaffos, 2014)
BACKGROUND: Chronic Obstructive Pulmonary Diseases (COPD) is estimated to rank fifth in burden of disease and third in terms of mortality by 2020 worldwide. It is characterized by chronic inflammation and non-fully reversible airflow obstruction, causing structural changes in the lungs that can be demonstrated by a post bronchodilator FEV1/FVC ratio <70%. MATERIALS AND METHODS: The sampling frame of the current study was the population of Tehran, the capital of Iran with the current population of nearly 8.1 million. A stratified cluster sampling strategy with proportional allocation within strata was used in this study. The target population was all Tehran residents, aged 18 to 40 in one group and over 40 in another, in the year 2013. The stratification process of the sample according to the 22 municipal districts of Tehran city has been incorporated in the sampling process. Proportional to the number of households in the 22 districts, the appropriate number of clusters is weighted according to each district. The decision about the number of clusters is based on total sample size; mean household members; and logistical facilities for subject enumeration, transport, and examination. RESULTS: The overall COPD prevalence defined by the spirometric functional criteria was 10%, higher in men 12 (11.9%) than in women 15 (8.8%); the prevalence was significantly higher in subjects aged over 55 years (P =0.001). Only 10(3.7%) of these COPD patients had already been diagnosed by a physician. Of all subjects fulfilling the criteria for COPD according to the Burden of Obstructive Lung Disease (BOLD) guidelines (post bronchodilator FEV1/FVC<70%), 90(33.3%) had chronic productive cough, and 262(96.7%) had either long-standing cough, sputum production, recurrent wheeze, dyspnea, or attacks of shortness of breath. CONCLUSION: Due to the small sample size at this stage of project, conclusions should be drawn with caution. In this first epidemiological report in Tehran about COPD, a moderate prevalence of the disease was determined, and a high percentage of this figure had not been diagnosed before by a physician.